Biochemical Differentiation of Selected Indigenous Cattle Breeds in Nigeria (2018)
Variations in genetic resources are the basis for effective genetic improvement in farm animals. Population differentiation is used for objective choice of parental genotypes that constitutes new hybrids in crossbreeding. In Nigeria, population characteristics of some selected indigenous cattle breeds have not been fully documented. Therefore, biochemical differentiation of some selected indigenous cattle breeds in Nigeria was assessed using their blood protein polymorphism. Blood samples (5mL) were taken underneath the fail by venipuncture from 40 cattle randomly selected from each of the five selected breeds. The samples were subjected to cellulose acetate electrophoresis to determine the genetic variants of haemoglobin (Hb), carbonic anhydrase (CA) and transferrin (Tf) following standard procedure. Data were analyzed using allele frequencies and duster analysis. Allele frequencies ranged betweenO.10 (H b *) and 0.90 (HbB+), 0.11 (CAR) and 0.89 (C A ^) and 0.02 (T F) and 0.49 (T F ) across the breed. Two main dusters from the dendrogram were observed for each of Hb, CA and Tf. Genetic variants of transferrin were largest within breed which indicated the potential for selection